Employing a nondestructive method for the estimation of foliar area of quina (Cinchona officinalis) - Sueldo, Andrea (2022)
Leaf area is related to tree growth, water balance, and mechanical resistance to physical and biotic agents. Given its importance, the purpose of the study was to compare two nondestructive methods of leaf area estimation using the free software ImageJ vs. graph paper in seedlings of quina tree. Three young and mature leaves were evaluated on 18 quina seedlings. Descriptive statistics were obtained, and both methods were compared using the Kruskal–Wallis test, and a regression equation was estimated based on leaf width and length.